1990
DOI: 10.2739/kurumemedj.37.265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological evaluation of early cancer in the gastric cardia.

Abstract: We report 9 rare cases (7 males and 2 females) of early gastric cancer of the esophagogastric junction. From 1976 to 1988, 1308 cases of gastric cancer were resected in our Institute. Of these, 479 (36.6%) cases were early gastric cancer. Among all 479 early gastric cancers, 9 (1.9%) were located within 2 cm of the esophagogastric junction on the lesser carvature and/or posterior wall of the cardia. This represents 11.7% (9/77) of the cases of cancer at the esophagogastric junction. This incidence contrasts wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…A recent detection rate of early gastric cancer has been reached to about 50% (Nagata et al 1983). However, upper gastric cancer, including cardia cancer, the rate for early gastric cancer was 12% in our recent study (Tanaka et al 1990), in comparison with 4% for Europe. The prognosis for gastric adenocarcinoma invading the esophagus is generally poorer than for adenocarcinoma in the middle or lower third of the stomach due to the inherent anatomical characteristics, such as a large tumor size and, frequently, a wide distribution of lymph node metastases to both mediastinal and abdominal regions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A recent detection rate of early gastric cancer has been reached to about 50% (Nagata et al 1983). However, upper gastric cancer, including cardia cancer, the rate for early gastric cancer was 12% in our recent study (Tanaka et al 1990), in comparison with 4% for Europe. The prognosis for gastric adenocarcinoma invading the esophagus is generally poorer than for adenocarcinoma in the middle or lower third of the stomach due to the inherent anatomical characteristics, such as a large tumor size and, frequently, a wide distribution of lymph node metastases to both mediastinal and abdominal regions.…”
Section: Discussioncontrasting
confidence: 56%
“…The most important surgical factor to improve the prognosis is the treatment of stage i gastric cancer invading the esophagus, since this is now curable by an extended radical operation mainly by a left thoracoabdominal approach. In the present study, the 5 year-survival rate in stage III was 12% for Group 1 and 46% for Group 2 which usually underwent more radical operations including combined resections of the diaphragm and lymphadenectomy beyond the paraaortic lymph nodes (Hashimoto et al 1990). Orel et al (1981) reported the disrupted anastomosis and cardiorespiratory fairure accounted for most of the postoperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 46%
“…3,15 In a multicenter clinicopathological study of 495 Chinese patients with EGC of the cardia, lymph node metastasis was not detected in 193 intramucosal (M2 [tumor limited to the lamina propria, without involving the muscularis mucosae] and M3 [tumors involving the muscularis mucosae]) carcinomas, 14 mixed mucinous adenocarcinomas with intestinal adenocarcinomas, and 10 rare carcinoma variants. 15 Even though EGC of the cardia showed more frequent submucosal invasion, 4,14,15,17 the risk of lymph node metastasis was also significantly lower in both superficial and deep submucosal carcinomas, compared with EGC at non-cardiac locations at the same stage. 15 This was especially true for rare variants of EGC in the cardia with frequent submucosal invasion.…”
Section: Introductionmentioning
confidence: 98%
“…Previous investigations of lesions in the gastric cardia have been focused primarily on nonneoplastic and neoplastic glands, whereas very few studies have scrutinized the muscularis mucosae (MM) and submucosa in the gastric cardia. [1][2][3][4] Yet until now, there have been no well-documented reports on the histopathological characteristics of the MM and submucosa in the gastric cardia. However, this line of histopathologic information is critically important for the appropriate clinical management of patients with gastric cardiac carcinoma and for a thorough understanding of the physiology and pathology of the gastric cardia.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cardia is a narrow region of the proximal stomach immediately distal to the gastroesophageal junction (GEJ). Previous investigations of lesions in the gastric cardia have been focused primarily on non‐neoplastic and neoplastic glands, whereas very few studies have scrutinized the muscularis mucosae (MM) and submucosa in the gastric cardia 1‐4 . Yet until now, there have been no well‐documented reports on the histopathological characteristics of the MM and submucosa in the gastric cardia.…”
Section: Introductionmentioning
confidence: 99%